Barriers to Buprenorphine Expansion in Ohio: A Time-Elapsed Qualitative Study. Issue 3 (27th May 2019) - Molfenter, Todd; Fitzgerald, Maureen; Jacobson, Nora; McCarty, Dennis; Quanbeck, Andrew; Zehner, Mark
ABSTRACT: Buprenorphine partial opioid agonist pharmacotherapy, a key treatment for opioid use disorders (OUDs), is underutilized in the United States. Qualitative interviews, conducted in 2012/2013 and repeated in 2015, identified systemic barriers to providing buprenorphine treatment in Ohio. A representative sample of Ohio's Alcohol, Drug Abuse and Mental Health Services (ADAMHS) county boards ( n = 18) was selected based on percentage of OUD admissions, density of buprenorphine prescribers, and county board area population. Boards reported that the barriers to the use of buprenorphine in 2012/2013 included (1) negative attitudes toward the use of buprenorphine among substance use disorder treatment providers; (2) a lack of prescribers; and (3) lack of funding. The 2015 interviews suggested that the lack of prescribers surpassed lack of funding as the main impediment to buprenorphine expansion. Negative provider attitudes were no longer problematic. Concerns about buprenorphine diversion, however, had emerged as a new barrier. This article offers recommendations for future policy efforts to overcome these barriers and expand the use of evidence-based opioid treatments. It highlights the need for payers and policymakers to increase the number of buprenorphine prescribers to make best use of funding available to fight the opioid epidemic.